Quem é o responsável pela criança? Reflexões psicanalíticas sobre a parentalização dos avós - Amaro, Fernanda Aline Tavares (2015)
The family configurations have diversified over the years and with that there was a consequent plurality in ways of organizing children s care. Focusing on families whose children are raised by grandparents, we ask ourselves about the functions assumed by them in these families and on the exercise of parental role in this scenario. This research was bolstered at the same time it was guided by clinical psychoanalytic method. Three families crossed the path of this work providing that theory and practice could be expanded and reinvent itself in order to create a singular knowledge. To understand the contemporary family issues, it was broached on historical, cultural and social aspects covered by traditional and modern family until the present day, which contributed to the multiplicity of familiar formats. Based on the fundamental encounter of the infant and the Other, it was discussed the primary parental role that could propitiate possible reflections on the role of grandparents, as well as on the constitution of its parentification process. Parenthood is approached in denatured form, it means, understood beyond the biological field, supporting thus the symbolic field. So, we discuss the impasses and embarrassment of these grandparents, aiming to understand the demands that join with them the grandchildren s creation and how parentification processes were being drawn in these families.